Breast Cancer - Miyoshi, Yasuo; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Breast Cancer, the official journal of the Japanese Breast Cancer Society, publishes articles that contribute to progress in the field, in basic or translational research and also in clinical research, seeking to develop a new focus and new perspectives for all who are concerned with breast cancer. The journal welcomes all original articles describing clinical and epidemiological studies and laboratory investigations regarding breast cancer and related diseases. The journal will consider five types of articles: editorials, review articles, original articles, case reports, and rapid communications. Although editorials and review articles will principally be solicited by the editors, they can also be submitted for peer review, as in the case of original articles. The journal provides the best of up-to-date information on breast cancer, presenting readers with high-impact, original work focusing on pivotal issues.
Keywords: Cancer research; Oncology; Surgery; Surgical oncology; Surgical Oncology; Oncology; Surgery; Cancer Research